2016
DOI: 10.1093/mutage/gew055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the DNA damage response in BEAS-2B and A549 cells exposed to titanium dioxide nanoparticles

Abstract: For some decades production of titanium dioxide nanoparticle (TiO-NP) has been increasing at a considerable rate; concerns as to the toxicity of these particles upon inhalation have been raised. Indeed, TiO-NPs have been shown to induce significant genotoxicity and to adversely affect both major DNA repair mechanisms: base excision repair (BER) and nucleotide excision repair (NER). The aims of the present study were to (i) compare the genotoxicity of TiO-NPs and their impact on DNA repair processes on A549 alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 61 publications
7
56
2
Order By: Relevance
“…In the present study, a significant increase of both DNA damages and MN frequencies was observed in the HUVECs exposed to the TiO 2 -NPs, with a clear doseeffect relationship (Figures 1 and 2). This is consistent with the findings of other groups in human lymphocytes, 30,38 BEAS-2B, 31 A549, [31][32][33] HepG2, 34 and HEK293 30 cells in vitro and in the mice PBMCs, 35 liver cells, 36,37 and lung cells 36 in vivo. Moreover, a very similar manner of dose-dependent and size-dependent effects was found as our previous work did in apoptosis assay, 10 On the other hand, accumulated DNA damage is now increasingly recognized as a causal factor in the initiation and progression of atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, a significant increase of both DNA damages and MN frequencies was observed in the HUVECs exposed to the TiO 2 -NPs, with a clear doseeffect relationship (Figures 1 and 2). This is consistent with the findings of other groups in human lymphocytes, 30,38 BEAS-2B, 31 A549, [31][32][33] HepG2, 34 and HEK293 30 cells in vitro and in the mice PBMCs, 35 liver cells, 36,37 and lung cells 36 in vivo. Moreover, a very similar manner of dose-dependent and size-dependent effects was found as our previous work did in apoptosis assay, 10 On the other hand, accumulated DNA damage is now increasingly recognized as a causal factor in the initiation and progression of atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the levels of Nrf2 protein were significantly elevated in the TiO 2 ‐NP‐treated HUVECs (Figure ). These data suggested that induction of oxidative stress might be an important biological mechanism by which TiO 2 ‐NPs pose a genotoxicity to HUVECs in culture and at a certain extent overwhelm/inhibit the DNA repair, as reflected in increase of MN, which are formed from the irreparable chromosomal damage, as other groups did in other human cells or animal models . In addition, our previous study found that TiO 2 ‐NP exposure could induce a significant apoptosis in HUVECs in culture .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…29 It is now known that the intracellular approach of apoptosis is mainly initiated by the induction of p53 as a response to DNA damage induced by genotoxic agents. 29 A number of studies have shown that nano-TiO 2 can induce DNA damage and adversely affect both major DNA repair mechanisms: base excision repair and nucleotide excision repair, showing a genotoxic potential to human cells 10,31,[42][43][44][45] and animal models. 24,46,47 We also found that the four sizes of nano-TiO 2 could induce significant DNA damages and micronuclei in human BEAS-2B cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…They are strong oxidants but also important agents modulating ROS-sensitive signaling pathways that lead to the cell death. Biola-Clier et al [145] report the ROS-mediated downregulation of DNA repair processes such as base excision repair and nucleotide excision repair. Toyooka et al [146], when examining toxicity of TiO 2 NPs (15 μg mL −1 ) to human A549 cells, concluded there was an increased H2AX histone phosphorylation that followed the oxidative stress-induced DNA double-strand breaks.…”
Section: Reviewmentioning
confidence: 99%